Dialektika Dalihan Na Tolu dalam Sense-making Ekologis: Analisis Literatur Sistem Komunikasi Kultural pada Pengambilan Keputusan Petani Desa Manyabar" - Khori Suci Maifianti; Rony Rahmat Hidayat Hasibuan; Devi Agustia; Annisa Fitri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The contemporary agricultural sector faces complex challenges due to global environmental volatility, demanding rapid adaptive responses from agrarian communities. This study aims to analyze in depth the role of Dalihan Na Tolu as a cultural communication system that bridges ecological sense-making in the collective decision-making of farmers in Manyabar Village, Panyabungan District, Mandailing Natal Regency. The research method employed is a descriptive qualitative library research through content analysis of reputable scientific literature spanning from 2018 to 2025. The synthesis results demonstrate that the triadic sociocultural network (Mora, Kahanggi, and Anak Boru) actively functions as a social anchor and an external information filter in facing ecological crises. Through two-way circular interactions, environmental uncertainty is successfully transformed into rational adaptation actions, such as irrigation management and planting schedule determination (marbuka saba). Quantification of empirical data reveals that the highest farmer compliance rate is in the resolution of irrigation water distribution conflicts (94.5%) and the lowest is in modern wage tariff penetration (78.5%). This indicates a clash between traditional kinship values and subsistent economic calculations in suburban areas. This study concludes that the flexibility of the Dalihan Na Tolu structure provides high sociological resilience for the local agricultural ecosystem against the onslaught of exploitative agrarian modernization.